PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Riko Levita Arnas; Wiyadi Wiyadi (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of this study was to analyze the effect of service quality and price perceptions on customer loyalty with customer satisfaction as an intervening variable. This research method is quantitative. The population in this study were all people who had used Rahayu Tour Travel services. The sample of this study was 140 respondents. This sampling technique uses purposive sampling. The data used in this research is primary data. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results of this study are that Service Quality and Price Perception have a positive and significant effect on Customer Loyalty. Service Quality and Price Perception have a positive and significant influence on Customer Satisfaction. Customer Satisfaction and Service Quality have a positive and significant influence on Customer Loyalty. Price Perception has a positive and significant influence on Customer Loyalty through Customer Satisfaction as a mediating variable. Keywords: Service Quality, Price Perception, Customer Loyalty, Customer Satisfaction